Música infantil y la comunicación oral en niños de la Institución Educativa Inicial N°348 Delia Perea, Quistococha, San Juan 2024 - Baneo Rucoba, Bella Margarita (2025)
The main purpose of this research was to establish the link between children's music level and the development of oral communication in children at Delia Perea Early Childhood Education Institution No. 348, located in Quistococha, San Juan District, during the year 2024. The study was developed under a quantitative approach, adopting a cross-sectional correlational design. The sample consisted of a total of 149 children. Observational technique was used to collect information, with the instrument being the observation guide. This instrument underwent rigorous validation by three specialists in the area. Regarding reliability, this was determined using Cronbach's alpha coefficient, after executing a pilot test. Statistical analyses showed a Student's t value equal to 8.978 and a bilateral significance value (p-value) of 0.000, a figure that is below the critical threshold of 0.05. Based on the statistical decision rule, these results allow us to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha), with a 95% confidence level. Therefore, we conclude that there is a statistically significant relationship between children's music and oral communication in the children evaluated.